2010
DOI: 10.1111/j.1365-2893.2009.01169.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of hepatitis C virus NS5A region in breakthrough patients during pegylated interferon and ribavirin therapy

Abstract: Investigating the evolution of the hepatitis C viral (HCV) genome in the small number of patients that experience viral breakthrough might shed light on the problem of resistance to interferon therapy. Within the HCV genome, sequence diversity of the viral nonstructural 5A protein-coding region (NS5A) has been linked to interferon responsiveness. We analyzed the temporal sequence changes within NS5A in genotype 1a patients: 6 breakthrough (BT), 12 sustained virologic responders (SVR) and 12 non-responders (NR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…However, since these models were generated using only 40 sequences from 20 patients, it is critical to demonstrate that the interrelationships identified for these patients are representative of those for other patients. For this purpose, two predictive models were constructed using the same Virahep-C data set and tested using the HCV NS5A sequences from baseline specimens obtained from patients in the HALT-C study (131). Because no additional data were available for E2 from patients with NR and UR outcomes investigated in a single study, only the NS5A models were validated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, since these models were generated using only 40 sequences from 20 patients, it is critical to demonstrate that the interrelationships identified for these patients are representative of those for other patients. For this purpose, two predictive models were constructed using the same Virahep-C data set and tested using the HCV NS5A sequences from baseline specimens obtained from patients in the HALT-C study (131). Because no additional data were available for E2 from patients with NR and UR outcomes investigated in a single study, only the NS5A models were validated.…”
Section: Resultsmentioning
confidence: 99%
“…For some analyses, a total of 298 HCV 1a fulllength consensus polyprotein sequences from GenBank were used. In addition, full-length NS5A protein consensus sequences from 18 treatment-naïve patients (6 UR and 12 NR) identified through the HALT-C trial (131) were used as a test data set to validate the NS5A predictive models constructed from the Virahep-C data. A full listing of the GenBank accession numbers of all sequences used in this study can be found in the supplemental material.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It does not exclude the possibility, however, that the same region plays an important role in modulating the interaction with various host systems, including IFN responsiveness. It is also possible that the genetic flexibility of this region, especially IRRDR, is accompanied by compensatory changes elsewhere in the viral genome and that these compensatory changes affect overall viral fitness and responses to IFN therapy [25] .…”
Section: Discussionmentioning
confidence: 99%
“…This flexibility might play an important role in modulating the interaction with various host systems, including IFN-induced antiviral machineries. It is also possible that the genetic flexibility of IRRDR is accompanied by compensatory changes elsewhere in the viral genome and that these compensatory changes affect overall viral fitness and responses to IFNbased therapy (8,29,41). Also, it is worth noting that IRRDR is among the most variable sequences across the different genotypes and subtypes of HCV (25) whereas its upstream and downstream sequences show a higher degree of sequence conservation (15).…”
Section: Discussionmentioning
confidence: 99%